Immune cell imaging using multi-spectral optoacoustic tomography - Tzoumas, Stratis; Zaremba, Angelika; Klemm, Uwe; Nunes, Antonio; Schaefer, Karin; Ntziachristos, Vasilis (Optics Letters, 2014)
Multispectral optoacoustic tomography (MSOT) offers the potential to image in high-resolution cells tagged with optical labels. In contrast to single wavelength imaging, multispectral excitation and spectral unmixing can differentiate labeled moieties over tissue absorption in the absence of background measurements. This feature can enable longitudinal cellular biology studies well beyond the depths reached by optical microscopy. However, the relation between spectrally resolved fluorescently labeled cells and optoacoustic detection has not been systematically investigated. Herein, we measured titrations of fluorescently labeled cells and establish the optoacoustic signal generated by these cells as a function of cell number and across different cell types. We then assess the MSOT sensitivity to resolve cells implanted in animals. © 2014 Optical Society of America.
CRIS-Team Scopus Importer:2023-03-08